Effects of soaking biochar in biodigester effluent as soil improvers on soil characteristics and yield of water spinach (ipomoea aquatica) : - Theary, Pok (Can Tho University, 2017)
Contents: Effect of soaking biochar in biodigester effluent as soil improver on soil characteistics and yield of water spinach (Ipomoea aquatica)